Experimenting with an Ad Hoc wireless network on campus insights and experiences. - Toh, C.-K (Sigmetrics :performance evaluation review.)
Ad hoc wireless networks are new communication networks that can be dynamically formed and deformed on-the-fly, anytime and anywhere. User data is routed with the help of an ad hoc mobile routing protocol. Before the deployment of ad hoc mobile services, the communication performance of such networks has to be evaluated to demonstrate the practicality limits based on today's hardware and innovative communication software. This paper describes the realization of an ad hoc wireless testbed and the various experimental field trials performed on campus. In particular, throughput, end-to-end delay, route discovery time, and the impact of varying source packet size and beaconing intervals are examined.